STRATEGIC TRIANGLE SP4N-LAPOR! DALAM PENINGKATAN PELAYANAN PUBLIK PADA KEMENTERIAN PENDAYAGUNAAN APARATUR NEGARA DAN REFORMASI BIROKRASI - Ludiana Ludiana; Engkus Kustyana; Fitri Pebriani Wahyu (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2026)
The digital transformation of public services through SP4N-LAPOR! is intended to realize transparent and participatory governance. However, the high number of reports categorized as archived and the limitations in operational capacity have resulted in suboptimal complaint follow-up and have affected the effectiveness of public services. This study aims to analyze the management of SP4N-LAPOR! at the Ministry of Administrative and Bureaucratic Reform using Mark H. Moore’s Strategic Triangle Framework. This study employed a descriptive qualitative approach through observation, interviews with SP4N-LAPOR! administrators, officials of the Ministry of Administrative and Bureaucratic Reform, service users, and documentation studies. The findings indicate that SP4N-LAPOR! has generated public value through an integrated participation system and accessible digital public services. Nevertheless, the internalization of legitimacy at the technical level remains weak, as reflected in the suboptimal interagency coordination and inconsistent follow-up of public complaints. In addition, limitations in human resources, system performance, and budget allocation constitute the main obstacles to operational capacity. Unlike previous studies that primarily focused on technical effectiveness, this study emphasizes the interdependence between public value, legitimacy, and operational capacity in the governance of digital complaint systems. This study recommends strengthening human resources, developing AI-based systems, and improving bureaucratic coordination to enhance the sustainability of digital public complaint services.